Mortality due to respiratory cancers in the coke oven plants of the Lorraine coalmining industry (Houillères du Bassin de Lorraine). Issue 8 (August 1987) - Bertrand, J P; Chau, N; Patris, A; Mur, J M; Pham, Q T; Moulin, J J; Morviller, P; Auburtin, G; Figueredo, A; Martin, J
Abstract : The main activity of the Houillères du Bassin de Lorraine (Lorraine Collieries), employing 23, 000 operatives and executives, is coalmining. The coke production is carried out by two coke oven plants with a workforce of respectively 747 and 552 workers. The coal coking process entails the emission of noxious products such as polycyclic aromatic hydrocarbons (PAH) from the ovens. The influence of occupational exposure on mortality due to respiratory cancers, and particularly to lung and upper respiratory and alimentary tracts cancer, was investigated among a cohort of 534 male workers from the two coke oven plants who had retired from work between 1963 and 1982. The job history of each subject has been precisely reconstructed by indicating the duration of exposure on the ovens, close to the ovens, and in maintenance occupations. The cohort mortality has been analysed according to the method of indirect standardisation with reference to the French male population and by a case-control study concerning the consumption of tobacco per cohort. The mortality due to lung cancer is 2.51 times higher than expected. This excess of mortality differs, but not significantly, between the two coke oven plants (standardised mortality ratio equals 3.05 and 1.75 respectively). It is not significantly higher among subjects exposed for more than five years, directly exposed on the ovens or working near the ovens or at maintenance occupations on the ovens (SMR = 2.78), than among those exposed for less than five years (SMR = 2.35) or those not exposed at all. Even taking into account the excess of mortality due to lung cancers in the Moselle district (1.6 time that of France), the excess of lung cancers does not seem to be explained by the regional factor, or by tobacco and alcohol consumption. Although no significant relation was offered between lung cancer and the duration of exposure to PAH, even when taking smoking habits into account, the carcinogenic role of occupational nuisances cannot be excluded.